2017
DOI: 10.1159/000471920
|View full text |Cite
|
Sign up to set email alerts
|

While Isolated Periodic Limb Movement Disorder Significantly Impacts Sleep Depth and Efficiency, Co-Morbid Restless Leg Syndrome Mainly Exacerbates Perceived Sleep Quality

Abstract: Background: Restless leg syndrome (RLS) and periodic limb movement (PLM) disorder (PLMD) can affect sleep quality and interfere with daytime functioning. Whether the co-morbidity of RLS further worsens daytime symptoms, sleep architecture and quality in patients with PLMs, is not yet fully clarified. Methods: Sleep (polysomnography) and daytime symptoms of 47 drug-free patients, assigned to isolated PLMD or co-morbid RLS subgroups, were compared to controls in a retrospective cohort-study (n = 501). Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
2
10
0
1
Order By: Relevance
“…The sleep disturbance is considered the reason for psychosomatic distress in RLS patients [25]. Previous studies have also reported that PLMD patients have worse insomnia symptoms [31] and impaired sleep quality than good sleepers [11], which is consistent with our findings in this study. The PLMD patients exhibited sleep disturbance on PSG and in- somnia symptoms similar to those in the patients with RLS.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The sleep disturbance is considered the reason for psychosomatic distress in RLS patients [25]. Previous studies have also reported that PLMD patients have worse insomnia symptoms [31] and impaired sleep quality than good sleepers [11], which is consistent with our findings in this study. The PLMD patients exhibited sleep disturbance on PSG and in- somnia symptoms similar to those in the patients with RLS.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported elevated SCL-90-R domain scores in all but the I-S and PAR domains in RLS patients compared with healthy controls [17]; similar results were demonstrated in our study. A recent study reported similar depressive and anxiety symptoms between RLS and PLMD patients [11]. However, the patients with PLMD in our study demonstrated a higher SCL-90-R score only in the HOS domain.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…RLS is mainly a wake-related disorder, characterized by an irresistible need to move the legs, usually accompanied by unpleasant sensations which begins or worsen during inactivity, especially in the evening/night, and improves or disappears by movement [44]. On the other hand, PLMD is a sleep-related condition, appearing mainly in the lower limbs and involving stereotyped involuntary movements (periodic limp movement-PLM) such as the extension of the big toe, often combined with a partial flexion of the ankle, the knee, and in some cases, the hip; those symptoms are often associated with cortical and/or autonomic arousals or with an awakening affecting significantly the patients quality of sleep [45].…”
Section: Sleep Related Movement Disordersmentioning
confidence: 99%